Diastereoselective reversible C–C bond exchange of oxindole–thiazolidienediones for dynamic combinatorial chemistry. Issue 47 (18th November 2022) - Gorai, Ananta; Chakraborti, Gargi; Basak, Soumya Jyoti; Dash, Jyotirmayee
Abstract : A metal and organic catalyst free diastereoselective aldol exchange under physiological conditions, suitable for the generation of dynamic combinatorial libraries (DCLs) has been described. Abstract : We herein describe a diastereoselective aldol exchange involving isatins and thiazolidinediones, providing oxindolyl-thiazolidienediones in aqueous media at pH 6. This equilibrium can also be achieved with oxindole exchange as well as cross-exchange within reasonable timescales. These metal and organic catalyst free reversible reactions provide a unique opportunity for the evolution of dynamic combinatorial libraries (DCLs) for target directed dynamic combinatorial chemistry (DCC) and system chemistry.